ONLINE PURCHASE DECISIONS AND BRAND IMAGE BASED ON SHOPEE AD EFFECTIVENESS WITH EPIC MODEL - Kundana, Dedi; Taridi, Taridi; Julianti, Mega (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study investigates the impact of advertising effectiveness on online purchase decisions on e-commerce platforms, focusing on Shopee, using the EPIC Model (Empathy, Persuasion, Impact, and Communication). It also examines the moderating role of brand image in this relationship. Employing a quantitative approach with descriptive and causal methods, data were collected through questionnaires distributed to active Shopee users. The data were analyzed using the Partial Least Squares (PLS) model to assess the relationships between advertising effectiveness, brand image, and purchase decisions. The findings indicate that advertising effectiveness significantly and positively influences online purchase decisions. Furthermore, brand image plays a crucial role in strengthening the relationship between advertising effectiveness and purchase decisions, highlighting its importance in enhancing the impact of advertisements on consumer behavior. This study emphasizes the need for e-commerce platforms to implement effective advertising strategies and cultivate a strong brand image to foster consumer loyalty and drive purchasing decisions. These insights offer valuable guidance for marketers to optimize advertising outcomes in competitive e-commerce environments.